(untitled) (Research, Society and Development, 2022)
The development of beverages with differential characteristics is mandatory, due to changes in the food habits of the population. The production of ready-to-drink fruit juices presents an interesting process for the shelf life extension, integral utilization of the fruits and the development of new products. The introduction of Cerrado fruit in this segment increases the visibility of these native species that are still unexploited. This study aimed to evaluate the bioactive compound stability of juices (marolo, cagaita and mixed: marolo + cagaita) during the refrigerated storage. The content of the vitamin C, total phenolics and antioxidant activity (auto-oxidation of the β-carotene/linoleic acid system, ABTS •+ and DPPH• free scavenging radical) in the juices were determined during the storage. The use of marolo and cagaita in the development of ready-to-drink beverages was suitable. A reduction in the vitamin C, total phenolics and antioxidant activity (evaluated by three methodologies) was observed during the 90 days. Considerable bioactive retention was obtained, highlighting the importance of the Cerrado fruit juices production.